Try NerdPal! Our new app on iOS and Android

# Find the derivative of $\left(x^4+2\right)^2\left(x^3+4\right)^4$

## Step-by-step Solution

Go!
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

### Videos

$8x^{3}\left(x^4+2\right)\left(x^3+4\right)^4+12x^{2}\left(x^4+2\right)^2\left(x^3+4\right)^{3}$
Got another answer? Verify it here!

## Step-by-step Solution

Problem to solve:

$\frac{d}{dx}\left(\left(x^4+\:2\right)^2\left(x^3\:+\:4\right)^4\right)$

Specify the solving method

1

Apply the product rule for differentiation: $(f\cdot g)'=f'\cdot g+f\cdot g'$, where $f=\left(x^4+2\right)^2$ and $g=\left(x^3+4\right)^4$

$\frac{d}{dx}\left(\left(x^4+2\right)^2\right)\left(x^3+4\right)^4+\left(x^4+2\right)^2\frac{d}{dx}\left(\left(x^3+4\right)^4\right)$

Learn how to solve differential calculus problems step by step online.

$\frac{d}{dx}\left(\left(x^4+2\right)^2\right)\left(x^3+4\right)^4+\left(x^4+2\right)^2\frac{d}{dx}\left(\left(x^3+4\right)^4\right)$

Learn how to solve differential calculus problems step by step online. Find the derivative of (x^4+2)^2(x^3+4)^4. Apply the product rule for differentiation: (f\cdot g)'=f'\cdot g+f\cdot g', where f=\left(x^4+2\right)^2 and g=\left(x^3+4\right)^4. The power rule for differentiation states that if n is a real number and f(x) = x^n, then f'(x) = nx^{n-1}. The power rule for differentiation states that if n is a real number and f(x) = x^n, then f'(x) = nx^{n-1}. The derivative of a sum of two or more functions is the sum of the derivatives of each function.

$8x^{3}\left(x^4+2\right)\left(x^3+4\right)^4+12x^{2}\left(x^4+2\right)^2\left(x^3+4\right)^{3}$
SnapXam A2

### beta Got another answer? Verify it!

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

$\frac{d}{dx}\left(\left(x^4+\:2\right)^2\left(x^3\:+\:4\right)^4\right)$